Porcine alveolar macrophages host proteins interacting with African swine fever virus p72 - Weng, Zhijun; Zheng, Xiaoyu; Liang, Yifan; Chen, Xiongnan; Peng, Qin; Zhang, Guihong; Gong, Lang; Zheng, Zezhong (Frontiers in Microbiology, 2024)
African swine fever virus (ASFV) spreads rapidly and has a mortality rate of up to 100% in domestic pigs, causing severe economic losses in the pig industry. The major capsid protein p72 of ASFV plays a crucial role in viral invasion and immune evasion. In this study, yeast two-hybrid screening was used to identify host proteins that interact with p72 in porcine alveolar macrophages (PAMs), identifying 13 interacting proteins including CD63, B2M, YTHDF2, FTH1, SHFL, CDK5RAP3, VIM, PELO, TIMP2, PHYH, C1QC, CMAS, and ERCC1. The interactions of these proteins with p72 have not been reported, except for VIM. These interactions were validated using confocal and immunoprecipitation techniques also.Additionally, enrichment and protein-protein interaction network analyses of the interacting proteins revealed their association with viral attachment, invasion, replication, assembly, and immune modulation.These findings contribute to an in-depth understanding of the function of p72 and provide new information for future studies.